Kidney Tumors in Children - Şefika Akyol (Galenos Publishing House, 2023)
Wilms tumor (WT) is an embryonal tumor of the kidneys. It is associated with many oncogenic genetic aberrations and congenital anomalies. Owing to worldwide clinical research and optimized patient care, curative therapy can be obtained in 90% of diagnosed children with WT. The decision of treatment mainly depends on stage, age, histological type, and genetic markers. Except for WT; congenital mesoblastic nephroma, clear cell sarcoma, malignant rhabdoid tumor, and renal cell carcinoma constitute 5% of kidney tumors. Herein, WT and other tumors of the kidney will be emphasized.